Environmental management systems experience among Latvian construction companies - Tambovceva, Tatjana; Geipele, Ineta (Technological and Economic Development of Economy, 2011)
At the present stage of development in Latvia, as well as around the world, essential influence on the enterprise work has the idea of sustainable development. The concept of sustainable development has become widespread amongst government agencies, politicians, corporations and other organizations throughout the world. By the end of 2007, around 129,031 organizations worldwide have implemented environmental management systems (EMS) and certified it according to ISO 14001. About 100 of them are located in Latvia and 40 of them are construction companies. There is a lack of national evaluations of ISO 14001 in many countries, but in many countries no complete lists of the national certified / registered sites exist at all. In Latvia a list of ISO 14001 sites has been complied and regularly updated by the Latvian association for Quality. In spite of the fact that in Latvia increase using of ideas of ecological manufacture and environmental management, nevertheless there has been no any serious scientific study of Latvian experience of ISO 14001. The purpose of this study is to describe experiences and effects of EMS in construction companies, based on study conducted for the construction industry in Latvia. The results show that ISO 14001 often leads to reduced environmental impact, especially in the area of waste. A strong driving force behind implementation is the expected improvement of the organizations’ images. Legal compliance tends to be difficult to implement, but on the other hand, it works well in daily practice. To develop EMS into Sustainability Management Systems, the two most important challenges are to improve the coordination between the EMS and the organizations’ strategies and to improve learning process and direct participation of all employees. Article in English. Aplinkos apsaugos vadybos sistemų taikymo patirtis Latvijos statybos įmonėse Santrauka. Šiuo Latvijos plėtros etapu, kaip ir visame pasaulyje, įmonių veiklą veikia tvarios plėtros idėjos. Tvarios plėtros koncepcija visame pasaulyje plačiai paplito tarp politikų, korporacijų, vyriausybinių ir kitų organizacijų. 2007 m. pabaigoje apie 129 tūkst. organizacijų visame pasaulyje įdiegė aplinkos apsaugos vadybos sistemą (AAVS) ir sertifikavo ją pagal ISO 14001 standartą. Iš to skaičiaus apie 100 įmonių yra įsikūrę Latvijoje, 40 iš jų yra statybos įmonės. Daugelyje šalių iš viso nėra įmonių, sertifikuotų pagal šį standartą. Latvijoje pagal ISO 14001 standartą sertifikuotų įmonių sąrašą sudaro ir nuolat atnaujina Latvijos kokybės asociacija. Nepaisant to, kad Latvijoje vis labiau plinta ekologinės gamybos ir aplinkosaugos valdymo idėjos, iki šiol nebuvo jokių rimtų mokslinių studijų apie Latvijos patirtį naudojant ISO 14001 standartą. Šio straipsnio tikslas – nustatyti aplinkos valdymo sistemos poveikį statybos įmonėms, remiantis tyrimais, atliktais Latvijos statybos pramonėje. Rezultatai parodė, kad ISO 14001 dažnai sumažina poveikį aplinkai, ypač taršą atliekomis. Stipri AVS įgyvendinimo varomoji jėga – noras pagerinti organizacijos įvaizdį. Sistemą įgyvendinti sudėtinga, tačiau tai pasiteisina kasdienėje veikloje. Norint AVS integruoti į tvarumo valdymo sistemą, AVS darbą reikia suderinti su organizacijos strategijomis, pagerinti mokymo procesą ir įtraukti visus darbuotojus. Reikšminiai žodžiai: aplinkos apsaugos vadybos sistema, ISO 14001, statybos pramonė, tvarioji plėtra, tyrimas. First published online 18 January 2012